An explanation for the purported excitation of piriform cortical neurons by N-acetyl-L-aspartyl-L-glutamic acid (NAAG). - Whittemore, E R (1989)
The excitation of piriform cortical neurons by iontophoresis of N-acetyl-L-aspartyl-L-glutamic acid (NAAG) isolated from rat brain is frequently cited as major support for the possible neurotransmitter role of NAAG in the CNS [ffrench-Mullen, J. M. H., Koller, K., Zaczek, R., Coyle, J. T., Hori, N. & Carpenter, D. O. (1985) Proc. Natl. Acad. Sci. USA 82, 3897-3900]. However, we have been unable to reproduce this observation using synthetic NAAG, and instead we offer an alternative explanation. In our experiments, iontophoresis of the sodium salt of synthetic NAAG did not induce single-unit spiking at sites in slices of rat piriform cortex that responded vigorously to L-glutamate. In contrast, iontophoresis of the potassium salt of synthetic NAAG or of potassium ions alone induced single unit activity. The responses to both NAAG/KCl and KCl alone were inhibited by L-2-amino-4-phosphonobutanoic acid and desensitized rapidly, as previously reported for NAAG. These results suggest that residual potassium ions, remaining after the original purification of NAAG, were responsible for the excitations attributed to NAAG.